Cognitive impairments associated with periventricular white matter hyperintensities are mediated by cortical atrophy. (16th May 2014) - Zi, W.; Duan, D.; Zheng, J.
<x xml:space="preserve">Abstract</x> Background Previous studies have shown that white matter lesions (WMLs) is an important risk factor for cognitive impairment, but the underlying mechanisms have not been clarified. Objective We tested the hypothesis that the cognitive impairments associated with periventricular white matter hyperintensities (PWMHs) on magnetic resonance imaging (MRI) would be mediated by the cortical thinning of corresponding area. Method Sixteen stroke‐ and dementia‐free subjects with PWMHs and 16 healthy control subjects were enrolled in this study. All participants underwent an examination of cognition, MRI‐based cortical thickness measurement and a MRI‐DTI scan. Then, the possible relationships among cognitive impairments, PWMHs and the topography of cortical thinning were analyzed. Results Comparing with the controls, the cognitive tests of the subjects with PWMHs showed significant decline in the domains of verbal fluency and executive function. After accounting for age, gender, years of education, and treatable vascular risk factors related to cognitive performance, cortical thickness had an independent influence on the cognitive impairments, especially in the frontal pole, orbitofrontal cortex, superior and middle frontal gyrus, superior and middle temporal gyrus, insula, and cuneus. Conclusions Our results suggest that the association between PWMHs and cognitive impairments is mediated by cortical thinning.